Protective action of Lactobacillus kefir carrying S-layer protein against Salmonella enterica serovar Enteritidis - Golowczyc, Marina Alejandra (2007)
Eight Lactobacillus kefir strains isolated from different kefir grains were tested for their ability to antagonize Salmonella enterica serovar Enteritidis (Salmonella enteritidis) interaction with epithelial cells. L. kefir surface properties such as autoaggregation and coaggregation with Salmonella and adhesion to Caco-2/TC-7 cells were evaluated. L. kefir strains showed significantly different adhesion capacities, six strains were able to autoaggregate and four strains coaggregated with Salmonella. Coincubation of Salmonella with coaggregating L. kefir strains significantly decreased its capacity to adhere to and to invade Caco-2/TC-7 cells. This was not observed with non coaggregating L. kefir strains. Spent culture supernatants of L. kefir contain significant amounts of S-layer proteins. Salmonella pretreated with spent culture supernatants (pH 4.5–4.7) from all tested L. kefir strains showed a significant decrease in association and invasion to Caco-2/TC-7 cells. Artificially acidified MRS containing lactic acid to a final concentration and pH equivalent to lactobacilli spent culture supernatants did not show any protective action. Pretreatment of this pathogen with spent culture supernatants reduced microvilli disorganization produced by Salmonella. In addition, Salmonella pretreated with S-layer proteins extracted from coaggregating and non coaggregating L. kefir strains were unable to invade Caco-2/TC-7 cells. After treatment, L. kefir S-layer protein was detected associated with Salmonella, suggesting a protective role of this protein on association and invasion.